Peluang Kewirausahaan Melalui Pengembangan Ide Produk Gula Aren Bubuk Di Desa Sindangsari Purwakarta - Dewi Puspasari; Yus Djunaedi Rusli; Alawiyah Nurhabibah (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2024)
Community Service Empowerment Activities aim at business management, as well as developing investment and economic productivity and Village potential, as well as obtaining profits or net profits to increase the village's original income and develop the maximum benefits of the Village community's economic resources. Another aim is to develop the idea for powdered palm sugar products, namely to help improve the economy of the people of Sindangsari Village in entrepreneurship by utilizing existing natural resources, and provide opportunities for Sindangsari Village to be better known by the wider community for its superior products, as well as helping advance sugar MSMEs. sugar palm in Sindagsari Village. This method of community service and empowerment activities consists of several stages, there are 3 (three) stages in the process of implementing this activity, namely: Trial of making ant sugar and determining packaging, Determining calculations and determining Cost of Production (HPP), and Holding seminars as one of the strategies for conveying the idea of powdered palm sugar products to the public. Sindangsari Village is one of the villages that produces palm sugar with quite good quality. This is our aim to develop entrepreneurial opportunities through the idea strategy of powdered palm sugar in Sindangsari Village. In practice, we utilize palm sugar production that has been molded to make the process easier, as well as symbiotic mutualism activities, where there are mutually beneficial parties, when people who are not palm sugar processors want to try making ant sugar, they can buy palm sugar first from entrepreneurs. Palm sugar